PENGARUH KERJASAMA INDONESIAN-JAPAN ECONOMIC PARTNERSHIP AGREEMENT (IJEPA) TERHADAP DOMINASI ASTRA HONDA MOTOR (AHM) DI INDONESIA - Sinaga, Rudi; Jamaan, Ahmad (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2023)
Indonesian-Japan Economic Partnership (IJEPA) is a trade and investment cooperation agreement that provides an opportunity to conduct export-import trade between Indonesia and Japan with low tariffs based on free trade. Japanese investment in Indonesia is generally in the manufacturing sector, Especially in the automotive and electronics industries. One form of the cooperation carried out by Indonesia within the IJEPA framework in the automotive sector is to form trade relations with PT. Astra International by establishing a two-wheeled vehicle assembly company under the name PT. Astra Honda Motor. Within the IJEPA framework, Indonesia provides the USDFS tariff scheme for Japan and Japan provides the MIDEC program for Indonesia. Therefore, the researcher drew the question "How does the IJEPA cooperation Influence the Domination of AHM in Indonesia?". To answer this question, the researcher used the Neorealism perspective. This perspective is considered appropriate because Japan and Indonesia are the main actors in the creation of IJEPA cooperation. This study To answer the question The researcher use the Perspective of Neorealism. This perspective is considered appropriate because Japan and Indonesia are the main actors in the creation of IJEPA cooperation. This research uses the Corporate Dominant theory as one of the theories to explain the dominance of AHM company in Indonesia after the IJEPA cooperation. In conducting this study, researcher used the qualitative research methods with library research methods. The result of the study show that Astra Honda Motor as one of the main players in the motorcycle industry in Indonesia gets a lot of benefits from the IJEPA cooperation and shows indication of industrial behavior towards monopoly while Indonesia does not get the benefit from the IJEPA cooperation due to the non-implementation of the MIDEC program. Keywords : IJEPA, AHM, MIDEC, USDFS Tariff Scheme